2011
DOI: 10.1099/mic.0.045856-0
|View full text |Cite
|
Sign up to set email alerts
|

The trans-Golgi SNARE syntaxin 6 is recruited to the chlamydial inclusion membrane

Abstract: Chlamydia trachomatis is an obligate intracellular pathogen that replicates within a parasitophorous vacuole termed an inclusion. The chlamydial inclusion is isolated from the endocytic pathway but fusogenic with Golgi-derived exocytic vesicles containing sphingomyelin and cholesterol. Sphingolipids are incorporated into the chlamydial cell wall and are considered essential for chlamydial development and viability. The mechanisms by which chlamydiae obtain eukaryotic lipids are poorly understood but require ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 57 publications
3
69
0
Order By: Relevance
“…In support of this notion, at least two Golgi-specific SNARES, including Syntaxin 6 and GS15 (Moore et al 2011;Pokrovskaya et al 2012), as well as vesicles containing the endocytic SNARES, Vamp3, Vamp7, and Vamp8, are recruited to the inclusion (Delevoye et al 2008;Paumet et al 2009). Interestingly, a subset of Incs contains motifs that display similarities to eukaryotic SNAREs, including IncA, CT813, and CT223 (Delevoye et al 2008;Paumet et al 2009).…”
Section: Interactions With Regulators Of Membranetrafficking Pathwaysmentioning
confidence: 86%
“…In support of this notion, at least two Golgi-specific SNARES, including Syntaxin 6 and GS15 (Moore et al 2011;Pokrovskaya et al 2012), as well as vesicles containing the endocytic SNARES, Vamp3, Vamp7, and Vamp8, are recruited to the inclusion (Delevoye et al 2008;Paumet et al 2009). Interestingly, a subset of Incs contains motifs that display similarities to eukaryotic SNAREs, including IncA, CT813, and CT223 (Delevoye et al 2008;Paumet et al 2009).…”
Section: Interactions With Regulators Of Membranetrafficking Pathwaysmentioning
confidence: 86%
“…Treatment of the infected host cells with chloramphenicol to inhibit bacterial www.intechopen.com protein synthesis abrogated trafficking of Syntaxin 6 to the inclusion suggesting that bacterial effectors are necessary to induce this recruitment. The depletion of Syntaxin 6 by siRNA did not significantly affect the development of the inclusion nor change the recruitment of sphingomyelin to the inclusion [Moore et al, 2011]. Therefore, the role f Syntaxin6 during Chlamydia infection remains unclear.…”
Section: Snare Proteins Are Recruited To the Inclusion Membranementioning
confidence: 99%
“…Syntaxin 6 is a SNARE protein that localizes to the trans-Golgi network (TGN) and likely plays a role in mediating the fusion of Golgi-derived vesicles with endosomes and/or lysosomes [Bock et al, 1997]. Recently, Hackstadt and co-workers showed that Syntaxin 6 relocates to the inclusion in a 18 hours post-infection [Moore et al, 2011]. Neither Syntaxin 4 nor Syntaxin 16 were found to localize to the inclusion suggesting that the recruitment of Syntaxin 6 was specific.…”
Section: Snare Proteins Are Recruited To the Inclusion Membranementioning
confidence: 99%
See 1 more Smart Citation
“…27,28,38 Previous studies show only the α-helical region facing the host cytoplasm is necessary for fusion 27 , however, biochemical properties and the structure of the soluble C-terminal domain of the IncA dimer have yet to characterized. …”
Section: Inclusion Protein Amentioning
confidence: 99%